(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
This article discusses the types and classifications of lacunae. Each of the types and classifications considered is used to describe differences between languages and cultures in a certain aspect. In addition to being the active words of this dialect, they are of great importance for enriching the vocabulary of the literary language.